2002
DOI: 10.1152/ajpcell.00607.2001
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinases mediate stretch-induced c-fos mRNA expression in myometrial smooth muscle cells

Abstract: . Mitogen-activated protein kinases mediate stretch-induced c-fos mRNA expression in myometrial smooth muscle cells. Am J Physiol Cell Physiol 283: C1530-C1539, 2002. First published July 3, 2002 10.1152 10. /ajpcell.00607.2001 indicates that stretch of the uterus imposed by the growing fetus contributes to the onset of labor. Previously we have shown that mechanically stretching rat myometrial smooth muscle cells (SMCs) induces c-fos expression. To investigate this stretch-induced signaling, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(111 citation statements)
references
References 48 publications
7
102
0
Order By: Relevance
“…Myometrial ERK2 phosphorylation increased significantly with advancing GA in accordance with previously reported results in the pregnant rat uterus (Oldenhof et al 2002, Serrano-Sanchez et al 2008. We observed no change in ERK1/2 phosphorylation in the myometrium with labor, which agrees with a previous report on the rat myometrium (Oldenhof et al 2002) but differs from that of Li et al (2003) who reported increased ERK2 phosphorylation in the rat uterus during labor.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Myometrial ERK2 phosphorylation increased significantly with advancing GA in accordance with previously reported results in the pregnant rat uterus (Oldenhof et al 2002, Serrano-Sanchez et al 2008. We observed no change in ERK1/2 phosphorylation in the myometrium with labor, which agrees with a previous report on the rat myometrium (Oldenhof et al 2002) but differs from that of Li et al (2003) who reported increased ERK2 phosphorylation in the rat uterus during labor.…”
Section: Discussionsupporting
confidence: 93%
“…We observed no change in ERK1/2 phosphorylation in the myometrium with labor, which agrees with a previous report on the rat myometrium (Oldenhof et al 2002) but differs from that of Li et al (2003) who reported increased ERK2 phosphorylation in the rat uterus during labor. While total ERK protein levels do not appear to change in the rat myometrium with pregnancy or labor (Li et al 2003), we saw a decrease in total ERK in human myometrium with advancing gestation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The stretch unit consists of a computer-controlled vacuum unit and a base plate to hold the 6-well culture dishes, which is placed in a humidified incubator with 5% CO 2 at 37°C. Static strain was applied by deforming the membrane with 150 mm Hg of vacuum pressure, which produces a maximal 25% stretch equal to the average 10% elongation (29). Control cells were cultured under identical conditions but remained stationary.…”
Section: Application Of Static Stretchmentioning
confidence: 99%
“…Mechanical stretch of the rat uterus stimulates myometrial cell hypertrophy (Douglas et al 1988) via a mechanism involving integrin/focal adhesion/MAPK cascades (Macphee & Lye 2000). Activation of MAPKs is necessary for optimal stretch-induced c-fos expression (Oldenhof et al 2002). In addition, the spatial expression of MAPK p38 and ERK-1/2 in conjunction with ATF2 isoforms within the human uterine corpus during pregnancy and labor is likely to be important in preparation of the uterus for labor (Otun et al 2005).…”
Section: Mapk-signaling Pathwaymentioning
confidence: 99%